2017
DOI: 10.1111/tpj.13519
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 2B‐beta (eIF2Bβ), a new class of plant virus resistance gene

Abstract: SUMMARYRecessive resistances to plant viruses in the Potyvirus genus have been found to be based on mutations in the plant eukaryotic translation initiation factors, eIF4E and eIF4G or their isoforms. Here we report that natural, monogenic recessive resistance to the Potyvirus Turnip mosaic virus (TuMV) has been found in a number of mustard (Brassica juncea) accessions. Bulked segregant analysis and sequencing of resistant and susceptible plant lines indicated the resistance is controlled by a single recessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…Through the intimate virus-host interactions, viruses remodel cellular membranes, hijack cellular pathways and co-opt diverse host factors to accomplish their life cycle (Wang, 2015;Hyodo and Okuno, 2016;Nagy, 2016). Genetic resistance is the preferred strategy for the control for viral infection (Shopan et al, 2017). Molecular identification of host factors and elucidation of their functional roles in the viral infection process could assist in the development of novel genetic resistance to viral disease (Wang and Krishnaswamy, 2012;Wang, 2015;Sanfac ßon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Through the intimate virus-host interactions, viruses remodel cellular membranes, hijack cellular pathways and co-opt diverse host factors to accomplish their life cycle (Wang, 2015;Hyodo and Okuno, 2016;Nagy, 2016). Genetic resistance is the preferred strategy for the control for viral infection (Shopan et al, 2017). Molecular identification of host factors and elucidation of their functional roles in the viral infection process could assist in the development of novel genetic resistance to viral disease (Wang and Krishnaswamy, 2012;Wang, 2015;Sanfac ßon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A core set of EIFs is conserved to facilitate the assembly of a translation-competent ribosome at the initiation codon of a mRNA [38]. An increasing number of studies have shown that plant EIFs play roles in stress resistance, such as eiF (iso)4E in B. rapa [39] and eif2Bbeta in B. juncea [40] in response to TuMV. In the present study, two isoforms of EIF, 6 and 3 L, were downregulated in response to drought stress, while five isoforms of EIF, 5A, 6, 3B, 3C, and 3 L, accumulated in the drought-stressed wheat seedlings pretreated with exogenous ALA. Eukaryotic translation initiation is a highly regulated and complex stage of gene translation, which requires the action of at least 13 core initiation factors and five auxiliary factors [38,41].…”
Section: Discussionmentioning
confidence: 99%
“…retr01 represents the first mapped recessive gene in Brassica species 25 ; other recessive genes from B. rapa include rnt1 and trs, which were mapped to R6 and A4, respectively 26,27 . Using bulked segregant analysis by sequencing (BSA-seq), Shopan et al 28 identified another recessive gene, retr03, in B. juncea. These mapping studies have facilitated the isolation of candidate genes.…”
Section: Turnip Mosaic Virusmentioning
confidence: 99%